Protrusion-Mediated Signaling Regulates Patterning of the Developing Nervous System - Moore, Rachel E.; Clarke, Jon; Alexandre, Paula (Frontiers in Cell and Developmental Biology, 2020)
During brain development the tissue pattern and specification are the foundation of neuronal circuit formation. Contact mediated lateral inhibition is well known to play an important role in determining cell fate decisions in the nervous system by either regulating tissue boundary formation or the classical salt and pepper pattern of differentiation that results from direct neighbouring cell contacts. In many systems however, such as the Drosophila notum, Drosophila wing, zebrafish pigmented cells and zebrafish spinal cord the differentiation pattern occurs at multiple cell diameter distances. In this review we discuss the evidence and characteristics of long distance patterning mechanisms mediated by cellular protrusions. In the nervous system cellular protrusions deliver the Notch ligand Delta at long range to prevent cells from differentiating in their vicinity. By temporal control of protrusive activity this mechanism can pattern differentiation in both space and time.